Municipal Wastewater By-Products Utilisation (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2025)
The challenges of mitigating climate change today require innovative and sustainable solutions to reduce carbon dioxide (CO2) emissions. Wastewater sludge, a byproduct of the wastewater treatment process, presents a valuable resource for contributing to emission reduction and the circular economy. This study analyzes the utilization of wastewater sludge with a dual-focus approach: biogas production as a short-term solution and the manufacturing of construction materials as a long-term strategy. Biogas generation provides an immediate method for energy recovery, reducing dependence on fossil fuels, while the use of sludge in cement and concrete production offers a sustainable alternative to energy-intensive traditional materials. The study evaluates the environmental and economic impacts of these methods, emphasizing their role in reducing CO2 emissions and addressing issues such as waste accumulation and soil degradation. A system model is developed using Stella Architect to assess the feasibility and scalability of these approaches. The findings suggest that large-scale implementation of wastewater sludge utilization can play a crucial role in climate change mitigation and resource efficiency. However, further research is necessary to enhance technological advancements, optimize costs, and support broader global adoption.